The Impact of Using A Reciprocal Teaching Strategy on Reading Comprehension By Prospective Teachers - Satriani; Munawir, Ahmad; Khair, Ummul; Putriani, Nur (ETDC: Indonesian Journal of Research and Educational Review, 2022)
The goal of this study was to improve students' reading comprehension using a Reciprocal Teaching Strategy in the fourth semester of IAI As'adiyah Sengkang's English education. The researcher used a pre-experimental design that included a pretest and a posttest. The sample comprised of 20 students drawn from IAI As'adiyah Sengkang's fourth semester English education students utilizing a cluster random selection approach. This study used a 20-item multiple-choice reading test as the research tool. Pre-test and post-test data were obtained. The data analysis revealed that the mean score of the students' pre-tests was 59, 29 and the mean score of the post-test was 77,62. It was discovered that pupils' reading comprehension improved after undergoing Reciprocal Teaching treatment (0.05). The researcher concluded that Reciprocal Teaching Strategy was appropriate in teaching reading comprehension at IAI As'adiyah Sengkang's fourth semester of English education. The reciprocal Teaching technique can be used as an alternative strategy in the teaching and learning process by English teachers and other scholars.